Franchising - D.E. Visuals (Firm) (Sunrise, FL. : D.E. visuals, 2010)
Discusses the franchising industry structures of product-trade name and business-format franchises. Outlines both the advantages and disadvantages of an entrepreneur going into business as a franchise compared to being an independent operation. Includes in-store footage and interviews with franchisors as to why they elected to expand operations through franchising rather than internally financed growth
Title from title screen
DVD format
Keywords: Franchises (Retail trade); Retail trade; Business